Multiscale 3D Virtual Dissections of 100-Million-Year-Old Flowers Using X-Ray Synchrotron Micro- and Nanotomography. (7th January 2014) - Moreau, Jean-David; Cloetens, Peter; Gomez, Bernard; Daviero-Gomez, Véronique; Néraudeau, Didier; Lafford, Tamzin A.; Tafforeau, Paul
Abstract A multiscale approach combining phase-contrast X-ray micro- and nanotomography is applied for imaging a Cretaceous fossil inflorescence in the resolution range from 0.75 μm to 50 nm. The wide range of scale views provides three-dimensional reconstructions from the external gross morphology of the inflorescence fragment to the finest exine sculptures of in situ pollen. This approach enables most of the characteristics usually observed under light microscopy, or with low magnification under scanning and transmission electron microscopy, to be obtained nondestructively. In contrast to previous tomography studies of fossil and extant flowers that used resolutions down to the micron range, we used voxels with a 50 nm side in local tomography scans. This high level of resolution enables systematic affinities of fossil flowers to be established without breaking or slicing specimens.